Peningkatan Keaktifan Siswa Pada Pembelajaran Matematika Melalui Strategi Student Team Achivemet PTK Bagi Siswa Kelas VIIB SMP Islam Ngesrep Tahun 2014/2015 - Susanti, Ika Malina (2016)
The research to increase student activity in the learning of mathematics for students of Islamic junior class Ngesrep VIIB 2014/2015 school year through the Student Team Achievement Division strategy. This research is a class act consisting of two cycles, each cycle consisting of three phases namely planning, action and observation, and reflection and evaluation. Data obtained in the form of a percentage increase in the activity at the end of the first cycle and at the end of the second cycle. Technique data analysis was done by using interactive analysis. The results showed an increase in activity of students in the learning of mathematics. Increased activity of students can be seen from the increase in the indicators include: 1) the willingness of students to ask before action after action 5.55% and 55.55%, 2) the willingness of students in answering questions before the actions 11.11% and after 72 action, 22%, 3) the willingness of students do exercises in front of the class before the action after the action of 0% and 66.66%, 4) the willingness of students to express their opinions before the action after the action of 0% and 55.55%. Based on the description above concluded that the implementation of the strategy Student Team Achievement Division on mathematics learning can enhance students' active.